An improved equation for predicting Canadian non-commodity exports - Patrick Alexander; Jean-Philippe Cayen; Alex Proulx (Bank of Canada, 2017)
We estimate two new equations for Canadian non-commodity exports (NCX) that incorporate three important changes relative to the current equation used at the Bank of Canada. First, we develop two new foreign activity measures (FAMs), which add new components to the FAM currently used at the Bank of Canada. The first measure adds US exports and US government expenditures, and the second adds US industrial production. These new FAMs calibrate the weights on the various components based on the 2014 World Input-Ouput Database to avoid the instability problem that arises when the equations are estimated. Second, we add a new variable to the equations, the trend of Canada's manufacturing share of output, to control for structural or competitiveness factors that affect Canada's global import market share. Third, the relative price of exports is determined by a new measure of the Canadian real effective exchange rate developed by Barnett, Charbonneau and Poulin-Bellisle (2016). We find that the new equations improve the in-sample fit and the out-of-sample forecast accuracy relative to the current equation specified in "LENS", a forecasting model used at the Bank of Canada.
Keywords: F10; F14; F17; 330; Balance of payments and components; Exchange rates; International topics